Pengolahan Sampah Kertas Menjadi Bahan Baku Industri Kertas Bisa Mengurangi Sampah di Indonesia - Saputra, Achmad Zaky; Fauzi, Ah. Sulhan (Jurnal Mesin Nusantara, 2022)
Garbage is an actual problem faced by Indonesia along with the increasing population. Paper is one of the most generated wastes. Indonesia produces 67.8 million tons of waste annually. And produces 8.1 million tons of paper waste annually. The volume of paper waste every 2 years increases by 1%. Paper waste can be recycled by the paper industry. With this research, the management of paper waste is used as a raw material for the paper industry by utilizing the fiber contained in paper waste. In this effort it can be see that recycling waste management can reduce waste in Indonesia by up to 10.2% per year. By recycling paper waste, we maintain the balance of nature and prevent global warming.